2021
DOI: 10.1111/apt.16718
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: disease activity indices for immune checkpoint inhibitor‐associated enterocolitis

Abstract: Background: Although there is interest in developing pharmacotherapies for the treatment of immune checkpoint inhibitor-associated enterocolitis (ICIC), there is currently no consensus on how to optimally measure disease activity in this condition. Aims:To identify all scoring indices used for the measurement of disease activity in ICIC, assess their operating properties, and explore their potential utility as outcome measures. Methods:We searched MEDLINE, EMBASE and the Cochrane Library from inception to Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As a result, it has become a global refractory disease with worldwide shifting epidemiological characteristics. Previous studies have found that immune dysfunction contributes to the progression of UC 4 . Specifically, in B cells, UC patients showed an increasing percentage of CD23 B naive cells than the normal individuals, while intestinal CD11b + B Cells relieve colitis by secreting immunoglobulin A 5 , 6 .…”
Section: Introductionmentioning
confidence: 92%
“…As a result, it has become a global refractory disease with worldwide shifting epidemiological characteristics. Previous studies have found that immune dysfunction contributes to the progression of UC 4 . Specifically, in B cells, UC patients showed an increasing percentage of CD23 B naive cells than the normal individuals, while intestinal CD11b + B Cells relieve colitis by secreting immunoglobulin A 5 , 6 .…”
Section: Introductionmentioning
confidence: 92%
“…Full results from this systematic review have been previously published. 14 In brief, although 83% of included studies reported histological findings associated with ICIC, no ICIC-specific histology indices were identified. Several instruments originally developed for ulcerative colitis (UC) have been applied to patients with ICIC, including the Geboes score, 15 Robarts Histopathology Index (RHI), 16 and Nancy index.…”
Section: Statement Generation and Systematic Reviewmentioning
confidence: 99%
“…These statements were informed by a systematic literature review conducted by our group. 14 We searched MEDLINE, Embase, the Cochrane CENTRAL Library, and conference proceedings from Digestive Disease Week, the United European Gastroenterology Week, the Society for Immunotherapy of Cancer Annual Meeting, and the American Society of Clinical Oncology National Meeting to identify studies evaluating disease activity in patients with ICIC. Search terms captured ICIs, diarrhea, and enterocolitis.…”
Section: Statement Generation and Systematic Reviewmentioning
confidence: 99%
“…Common Terminology Criteria for Adverse Events (CTCAE) grading for colitis or diarrhoea is commonly used for IMDC ( Table 1 ) [21] . However, there are currently no validated clinical, endoscopic, or histologic outcomes to assess disease activity in IMDC.…”
Section: Management In Case Of Incidental Digestive Symptoms ( Fig 1 )mentioning
confidence: 99%
“…However, there are currently no validated clinical, endoscopic, or histologic outcomes to assess disease activity in IMDC. Waiting for development and validation of reliable and dedicated outcome measures for IMDC, current IBD outcome measures may be also used to assess IMDC severity [21] . In patients with pre-existing IBD treated with ICI having digestive symptoms, similar management as for IBD relapse including stool cultures and Clostridioides difficile toxin testing as well as blood tests including cytomegalovirus PCR, may be useful [25 , 26] .…”
Section: Management In Case Of Incidental Digestive Symptoms ( Fig 1 )mentioning
confidence: 99%